Combination of 5‐Fluorouracil with Photodynamic Therapy: Enhancement of Innate and Adaptive Immune Responses in a Murine Model of Actinic Keratosis. (20th September 2022) - Anand, Sanjay; Heusinkveld, Lauren E.; Cheng, Cheng‐En; Lefatshe, Lefatshe; De Silva, Pushpamali; Hasan, Tayyaba; Maytin, Edward V.
Abstract: We previously showed that a combination of differentiation‐inducing agents (5‐fluorouracil [5FU], vitamin D3 or methotrexate) and aminolevulinate‐based photodynamic therapy (PDT) improves clinical responses by enhancing protoporphyrin IX (PpIX) photosensitizer levels and cell death. Here, we show that in addition to its previously known effects, 5FU enhances PDT‐induced tumor‐regressing immunity. Murine actinic keratoses were treated with topical 5FU or vehicle for 3 days prior to aminolevulinic acid application, followed by blue light illumination (~417 nm). Lesions were harvested for time‐course analyses of innate immune cell recruitment into lesions, i.e. neutrophils (Ly6G+) and macrophages (F4/80+), which peaked at 72 h and 1 week post‐PDT, respectively, and were greater in 5FU‐treated lesions. Enhanced infiltration of activated T cells (CD3+) throughout the time course, and of cytotoxic T cells (CD8+) at 1–2 weeks post‐PDT, also occurred in 5FU‐treated lesions. 5FU pretreatment reduced the presence of cells expressing the immune checkpoint marker PD‐1 at ~72 h post‐PDT, favoring cytotoxic T cell activity. A combination of 5FU and PDT, each individually known to induce long‐term tumor‐targeting immune responses in addition to their more immediate effects on cancer cells, may synergize to provide better management of squamous precancers. Abstract : Mechanisms of action when 5‐fluorouracil (5FU) and photodynamic therapy (PDT) are combined to treat squamous precancer lesions. 5FU inhibits thymidylate synthase, damages DNA and RNA and activates p53. 5FU also induces antitumor immunity by suppressing myeloid‐derived suppressor cells, activating damage‐associated molecules (DAMPs), recruiting immune cells and suppressing immune checkpoint receptors (PD‐1). Painless PDT (pPDT) exerts nonoverlapping effects. pPDT induces immunogenic cell death instead of apoptosis, thereby activating DAMPs and recruiting innate and adaptive immune cells. 5FU and PDT, each known to induce antitumor immunity in addition to their antimetabolite and cytotoxic effects, are therapeutically more effective when combined.